Clinical outcomes of gefitinib and erlotinib in patients with NSCLC harboring uncommon EGFR mutations: A pooled analysis of 438 patients. (October 2022) - Wang, Chunsheng; Zhao, Kewei; Hu, Shanliang; Dong, Wei; Gong, Yan; Li, Minghuan; Xie, Conghua
Highlights: Uncommon EGFR mutations exhibit favorable but inconsistent treatment responses and survival outcomes to gefitinib and erlotinib. Patients with compound EGFR mutations, especially those containing 19 deletion or L858R, had superior response and survival benefits compared to those with single uncommon EGFR mutation. Gefitinib showed a superior tumor response advantage and PFS benefit compared to erlotinib in the treatment of patients with uncommon EGFR mutations. Abstract: Background: The purpose of this study was to investigate the outcomes of gefitinib and erlotinib in patients with non-small cell lung cancer (NSCLC) with uncommon epidermal growth factor receptor (EGFR) mutations. Methods: Relevant researches were identified by a literature search of the PubMed database. Patients with EGFR mutations other than exon 19 deletion and L858R were eligible for the study. Clinical outcomes included objective response rate (ORR), progression free survival (PFS), and overall survival (OS). We categorized all uncommon EGFR mutations as: single uncommon EGFR mutations and compound mutations that containing 2 or more kinds of EGFR mutations. We also assessed outcomes in patients categorized by EGFR-TKIs: (1) gefitinib group; (2) erlotinib group. Results: A total of 438 patients with NSCLC harboring uncommon EGFR mutations were included in this study. The ORR for gefitinib and erlotinib was 43.8 %, with a median PFS (mPFS) of 6.00 months and a median OS (mOS) of 20.50 months. Patients with compound mutations had an ORR of 56.3 % and an mPFS of 8.10 months. Both of them were significantly better than these in patients with single uncommon EGFR mutation, which were 29.3 % and 3.90 months, respectively (odds ratio (ORa): 2.74, 95 % confidence interval (CI): 1.86–4.05, P  < 0.001; hazard ratio (HR): 0.58, 95 % CI: 0.48–0.71, P  < 0.001). Moreover, patients with compound mutations containing 19 deletion or L858R had a superior response and survival benefits compared to patients with other compound mutation patterns. In addition, the gefitinib group showed a favorable efficacy advantage ( P  = 0.003) and PFS benefit ( P  = 0.021) compared to the erlotinib group. Conclusions: Uncommon EGFR mutations exhibit favorable but inconsistent treatment responses and survival outcomes to gefitinib and erlotinib, which are closely related to the mutation pattern, the cooccurring partner mutant genes, and the type of EGFR-TKIs received.